Еssential Factors Of Etiopathogenesis In The Development Of Parodontal Diseases In Post-Menopasis Women (Eurasian Medical Research Periodical, 2023)
The structure of the intestine’s wall. liver and heart were studied in acute peritonitis and postoperative period. The experiment was performed on 25 male rabbits. Morphological changes were investigated using light microscopy with haematoxylin-eosin and Van Gison staining. It was shown that the development of acute peritonitis led to significant changes in the intestine. liver and heart. Inflammatory reaction with predominance of exudation was combined with dystrophic alteration in described organs. The changes arose towards the first day and lowered by the fifth day of postoperative period when regeneration processes developed.